The procrastination of Internet gaming disorder in young adults: The clinical severity. (August 2017) - Yeh, Yi-Chun; Wang, Peng-Wei; Huang, Mei-Feng; Lin, Pai-Cheng; Chen, Cheng-Sheng; Ko, Chih-Hung
Abstract: Young adults with Internet gaming disorder (IGD) usually postpone the tasks of their daily lives to engage in Internet gaming. This study evaluates the association between procrastination and IGD and the association between the negative consequences of IGD and procrastination. We recruited 87 individuals with IGD and 87 controls without a history of IGD. All participants underwent a diagnostic interview based on the DSM-5 IGD criteria to assess the clinical global score. They also completed questionnaires regarding IGD, procrastination, impulsivity, depression, and hostility. Young adults with IGD had higher levels of procrastination. Procrastination was positively associated with depression, hostility, and impulsivity. After controlling for depression, hostility, and impulsivity, procrastination was still found to be associated with IGD. Further, procrastination was positively associated with the clinical global impressions score among young adults with IGD. Procrastination is associated with IGD independent of depression, hostility, and impulsivity. Procrastination is also associated with the clinical severity of IGD. The results suggest that procrastination should be carefully evaluated and intervention should be taken with young adults with IGD. This intervention might attenuate the negative consequences of IGD. Highlights: Procrastination associated with IGD. The association was significant with control of depression, hostility, and impulsivity. Procrastination associated with clinical severity of IGD.